Legal Status of Bukaemas Transactions and Golden Gardening - Amin Awal Amarudin; Muhammad Adib Faqihuddin (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Gold is a precious metal that has a stable value and its selling value remains high in the gold market. Gold gardening is one of the gold investment trends that have lucrative advantages, so it arises how the legal status of investing in gold gardening and buying and selling gold in cash. This research method uses a research library that retrieves information from books, yellow books, and some supporting articles. Data analysis is done by collecting possible propositions and non-permissibe propositions. The results showed that in buying and selling gold in cash is allowed because gold has become an item in general, not a currency like in ancient times. While in gold gardening is not allowed on the grounds of violating the provisions of Shari'ah namely maysir and gharar. So that in doing gold gardening can cause mudharat for yourself and also others